Protection of the rights of consumers in sphere of crediting: legal compromise or its imitation? - Зеленова, Марина Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article describes the issues that arose in Ukraine due to the necessity of restructuring of consumer loans issued in foreign currency. It was noted that some of the blame for the situation that has developed in the field of consumer credit lies with the state and banks. Therefore, in the situation in Ukraine should be developed compromise solutions to this crisis. In this regard, were analyzed in a separate legislative initiative aimed at solving this problem. The first of these initiatives was analyzed the draft Law of Ukraine of 22 December 2014 "On protection of rights of consumers of financial services from the effects of the devaluation of the hryvnia", determined its strengths and weaknesses. After that was analyzed the draft law of Ukraine of 23 December 2014 "On restructuring of credits in foreign currency", which was later adopted as the Law of Ukraine from 7 July 2015 and had the same name. It was determined why the act has reverberated in the state and society. Analyzed also some proposals for the restructuring of consumer loans issued in foreign currency, proposed the draft law, elaborated by the Ministry of Finance of Ukraine jointly with the National Bank of Ukraine and the Independent Association of Ukrainian banks. At the end of the article were the comments and suggestions made to improve the criteria on the basis of which should be determined consumer loans subject to restructuring.